2014
DOI: 10.1249/mss.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Circumference Is Superior to Body Mass Index in Estimating Musculoskeletal Injury Risk

Abstract: AC is a better predictor of musculoskeletal injury risk than BMI in a large military population. Although absolute injury risk is greatest in 18- to 24-yr-old participants, the effect of obesity on injury risk is greatest in 25- to 34-yr-old participants. There is a dose-response relation between obesity and musculoskeletal injury risk, an effect seen with both BMI and AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…When fat accumulates in the abdominal region, it can be stored in the visceral region or the subcutaneous region. In addition to increased injury risk (15,16), VAT is an independent risk factor for cardiovascular disease and insulin resistance (3,4,9,11,17,21). In this population, this accumulation occurred at different thresholds, suggesting that excess fat will be preferentially distributed to the SAAT region before VAT region.…”
Section: Discussionmentioning
confidence: 96%
“…When fat accumulates in the abdominal region, it can be stored in the visceral region or the subcutaneous region. In addition to increased injury risk (15,16), VAT is an independent risk factor for cardiovascular disease and insulin resistance (3,4,9,11,17,21). In this population, this accumulation occurred at different thresholds, suggesting that excess fat will be preferentially distributed to the SAAT region before VAT region.…”
Section: Discussionmentioning
confidence: 96%
“…However, often it is argued that an injury-free fitness program is, by definition, an ineffective fitness program. Among all injuries incurred by military personnel, the largest proportion (ranging from 32%–63%) are associated with engaging PT and sports, and substandard fitness and body composition are consistent PT injury predictors 2427 . Previous reviews have examined injury incidence proportions attributable to PT in the military, with incidence proportions ranging from 16.3%–61.7% for women and 7.5%–50.7% for men in a variety of training contexts such as basic training, infantry, special warfare, and officer candidate schools 23 .…”
Section: Injury Risk In the Military And Association With Hift-rmentioning
confidence: 96%
“…The second paper cited (reference 27) is a story in the Air Force Times magazine 31 that discusses the conference about ECPs upon which the Bergeron paper 19 was based, and that anecdotal reports of injury were why the conference was convened. The Air Force Times article quotes one of the other Bergeron 19 paper’s authors (Dr. Francis O’Connor) as saying “the reason we are here is because of all of the anecdotal reports of injuries.” 31 However, anecdotal cases are inferior to systematic evaluations of injury risk with respect to more accurately characterizing the injury potential for sports and fitness activities.…”
Section: Injury Risk In the Military And Association With Hift-rmentioning
confidence: 99%
“…Furthermore, BMI, which was used as a measure of obesity in this study, may not be an accurate representation of obesity since it cannot distinguish between fat and lean mass. Nye et al (2014) suggested that waist circumference is a better measure than BMI for estimating musculoskeletal injury risk. The NHIS, unfortunately, has not collected waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the prevalence of injury characteristics and the relationship between BMI and injuries, but not by specific occupational groups. The prevalence of obesity is different by occupation and gender (Nye et al, 2014; Schulz & Sherwood, 2008), and each occupational group is likely to have different characteristics of injury. It would be worthwhile to investigate the prevalence of injuries by occupational group and gender.…”
Section: Discussionmentioning
confidence: 99%